Reconfiguring local food governance in an age of austerity: towards a place-based approach?. (July 2019) - Lever, John; Sonnino, Roberta; Cheetham, Fiona
Abstract: In this paper we examine the dynamic nature of local food governance by considering the potential for (and barriers to) developing a more robust approach that can enhance the socio-ecological resilience of the food system. Fusing insights from Eliasian sociology with the literature on local food governance, we focus on a region of northern England to explore understandings of "local food" and the problems local food actors encounter while working within and across the territorial boundaries of "the local". This is underpinned by an examination of the pressures local governments face as a result of financial austerity and competing neoliberal policy priorities that, we argue, undermine attempts to create synergies between diverse food system actors. We conclude by outlining the potential for developing a more relational approach to (and understanding of) place-based food governance. Highlights: The celebratory tone of local food governance literature is questioned. Attempts to create food system synergies are undermined by neoliberal governance. The number of cordinated positions within and across figurations exposes asymmetries of power. Relational interdependence across place highlights the potential for food system reform.